Uji Aktivitas Analgetik Ekstrak Etanol Daun Seledri (Apium Graveolens L. ) Terhadap Mencit Putih Jantan - Afifah Almasri (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2017)
Previous studies have found that celery leaves (Apium Gravieolens L.) have an analgesic effect. Substances that are efficacious as analgesics are flavonoids. This study aims to determine the analgesic effect of ethanol extract of celery leaves by increasing the dose of ethanol extract of celery leaves from previous researchers. A total of 9 test animals were divided into 5 treatment groups, namely the first group of test substances at a dose of 4mg/20gBW, the second group of test substances at a dose of 8mg/20gBW, and the third group of test substances at a dose of 16mg/20gBW. The test is carried out by giving a hot stimulus or Hot Plate at a temperature of 550C. The test animals were observed before and after the administration of the test material, 30th, 60th and 90th minutes. The response of the test animals was a decrease in the number of paw licking and jumping. The results of data analysis in the form of tables and graphs show that the ethanol extract of celery leaves can reduce the response of mice in licking their feet and jumping to hot stimuli. Statistical results show that by using the anava test. Where Fcount 0.85 ≤ Ftable 5.14 using α 0.01 which means that there is no significant difference between the 4 mg dose of celery leaf extract and 8 mg dose of celery leaf extract and 16 mg dose of celery leaf extract.